Development of an Adobe Illustrator Based Pop Up Book for Islamic Cultural History Learning - Titania Amilia Putri; Mazrur Mazrur; Slamet Riyadi (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study aimed to develop Adobe Illustrator-based Pop Up Book learning media for Islamic Cultural History (SKI) subjects and evaluate its feasibility in supporting students’ engagement and creativity in learning. The study was motivated by the low level of active participation among fourth-grade students at MI Darul Ulum Palangka Raya. This research employed a Research and Development (R&D) method using the 4D model: Define, Design, Development, and Dissemination. The participants consisted of fourth-grade students and an SKI teacher at MI Darul Ulum Palangka Raya. Data were collected through questionnaires, interviews, documentation, and observation. The instruments included expert validation sheets and teacher and student response questionnaires. The outcomes measured were media feasibility and user responses toward the developed media. The define stage involved analyzing students’ needs, curriculum, and learning characteristics. The design stage included preparing storyboards and validation instruments, while the development stage involved product testing and revision based on expert suggestions. The dissemination stage involved distributing the media to teachers and students. The results showed that the media obtained a material expert validation score of 98% and a media expert validation score of 97%, categorized as very feasible. Student responses reached 79.64% and teacher responses reached 75%, categorized as good. The data were analyzed descriptively using percentage analysis. These findings indicate that the developed media is feasible and has the potential to support more interactive and engaging SKI learning activities.